Estilos de aprendizaje en estudiantes varones y mujeres del sexto ciclo de una institución educativa estatal de Ventanilla - Mamani Segura, Rocio Maritza (2011)
The present investigation is a study of descriptive comparative type and of design non experimental transeccional. The purpose is to compare the active, reflexive, theoretical and pragmatic learning styles according to sex in males and women students of the sixth cycle - the first and the second high school-, of an educational institution of Ventanilla district. The used instrument was the questionnaire Honey-Alonso of learning styles (CHAEA), it was applied to a sample of 220 students, with ages between 12 to 16 years. The results of the present study showed that yes exist significant differences in the active style in favour of the women. As for the reflexive style, exist differences in favour of the women, but they are not significant. On the theoretical and pragmatic styles concluded that do not exist significant differences according to the sex.